ANALISA KEBUTUHAN RUANG PARKIR RUMAH SAKIT ISLAM IBNU SINA PAYAKUMBUH SUMATERA BARAT - Berty, Devit Delly; Kurniawan, Deddy; Dewi, Selpa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Parking is stopping and storing a vehicle for a while in a certain space. Vehicles may not move continuously, for a while or stop long enough. The purpose of this study, among others, is to determine the capacity of parking space requirements at Ibnu Sina Payakumbuh Islamic Hospital. For parking patterns in the modeling of parking spaces using a 45o parking pattern, to make it easier to maneuver the car in parking. The research was conducted at Ibnu Sina Payakumbuh Islamic Hospital street.Veteran No.14, Koto Baru, Balai Janggo, Payakumbuh City, West Sumatra. This road is ±11 meters wide and ±450 meters long. This road does not have a special parking lot, and this road does not have a shoulder, has sidewalks on both sides of the road and does not have parking signs. Where the results of the study obtained the volume of vehicles when parking for motorcycles most on Wednesday, March 29, 2023 as many as 117 vehicles / hour. And the volume of vehicles when parking for the most cars on Wednesday, April 05, 2023 as many as 59 vehicles / hour.